Chemical-weapon use in Syria: atrocities, attribution, and accountability. Issue 5 (2nd September 2019) - Koblentz, Gregory D.
ABSTRACT: International efforts to hold the government of President Bashar al-Assad accountable for the use of chemical weapons in the Syrian Civil War have entered a new phase. For the first time, the Organisation for the Prohibition of Chemical Weapons (OPCW), the international organization responsible for implementing the 1993 Chemical Weapons Convention, has been empowered to identify the perpetrators of chemical attacks in Syria. The Investigation and Identification Team (IIT), which was formed to conduct the OPCW's new attribution mission, has announced its intention to investigate and identify the perpetrators of nine chemical attacks in Syria, including the April 7, 2018, attack in Douma. This article reviews recent efforts to attribute chemical attacks in Syria, describes what we know about the nine incidents to be investigated, summarizes what is known about the Syrian government officials, military commanders, and chemical-warfare scientists suspected of being responsible for these attacks, discusses what to expect during the next phase of the attribution process, and offers insights into how the international community can move beyond attribution to accountability. Accountability is necessary to provide justice for victims and to prevent future incidents by demonstrating that perpetrators of chemical attacks will be identified and punished.